2018
DOI: 10.3389/fimmu.2017.01958
|View full text |Cite
|
Sign up to set email alerts
|

M1 and M2 Monocytes in Rheumatoid Arthritis: A Contribution of Imbalance of M1/M2 Monocytes to Osteoclastogenesis

Abstract: ObjectivesWe investigated the relationships among M1 monocytes, M2 monocytes, osteoclast (OC) differentiation ability, and clinical characteristics in patients with rheumatoid arthritis (RA).MethodsPeripheral blood mononuclear cells (PBMCs) were isolated from RA patients and healthy donors, and we then investigated the number of M1 monocytes or M2 monocytes by fluorescence-activated cell sorting. We also obtained and cultured CD14-positive cells from PBMCs from RA patients and healthy donors to investigate OC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 27 publications
(30 reference statements)
5
108
0
1
Order By: Relevance
“…[12][13][14][15]37 Several studies have reported that subtypes and inflammatory status of peripheral monocytes greatly influence the progress of inflammatory diseases. [16][17][18]38 For example, Cifani et al reported that AAD patients displayed the significantly increased CD14 ++ CD16classical monocytes in the peripheral blood. 15 In the present study, the percentage of CD14 + CD163 + CX3CR1 + M2-like monocytes were decreased in the AAD patients as compared with HD, leading to an increase in the ratio of M1/M2-like monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15]37 Several studies have reported that subtypes and inflammatory status of peripheral monocytes greatly influence the progress of inflammatory diseases. [16][17][18]38 For example, Cifani et al reported that AAD patients displayed the significantly increased CD14 ++ CD16classical monocytes in the peripheral blood. 15 In the present study, the percentage of CD14 + CD163 + CX3CR1 + M2-like monocytes were decreased in the AAD patients as compared with HD, leading to an increase in the ratio of M1/M2-like monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…M1-like monocytes express the CD68 + CCR2 + cell marker whereas M2-like monocytes express the CD163 + CX3CR1 + cell marker. [16][17][18] M1-and M2-like monocytes has been reported to be discrepantly presented in patients with diabetes, with the ratio of M1/M2-like monocytes being closely associated with disease severity. 16 However, the proBDNF expression pattern in M1-and M2like monocytes and in monocytes from AAD patients is not known yet.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage-mediated inflammation and tissue damage are features of many chronic inflammatory diseases (63,64). To date, C5orf30 has been associated with two autoimmune diseases, RA and primary biliary cirrhosis, which have a shared pathogenesis, including the skew of macrophages to the inflammatory phenotype and disease progression associated with increased local recruitment and activation of macrophage and fibroblast cells (17,18,65,66). In this study, we show C5orf30 to be inversely correlated with disease activity, systemic inflammation, and local TNF levels in early RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…We uncover new insights into C5orf30 physiology and discover differential regulation of C5orf30 in M1-and M2-like macrophages. An imbalance of macrophage M1-M2 polarization has been associated with RA and multiple inflammatory conditions (13)(14)(15)(16)(17). Identification of the proteins associated with the dynamic changes of macrophages is crucial for revealing the molecular basis of disease progression (18,19) and to fuel the innovation pipeline for novel therapeutic strategies targeting inflammatory resolution rather than suppression (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The degree of synovial macrophage infiltration correlates with the severity of RA (29). Monocytes can differentiate into classically activated pro-inflammatory M1 macrophages to aggravate the RA symptom and alternatively into anti-inflammatory M2 macrophages to improve the RA phenotype (30). Therefore, we determined whether HJ influences the infiltration of articular macrophages and the M1/M2 subsets in cIA mice.…”
Section: Hj Inhibits the Expression Of Pro-inflammatory Mediators In mentioning
confidence: 99%